2011
DOI: 10.3945/ajcn.110.007179
|View full text |Cite
|
Sign up to set email alerts
|

Micronized ferric pyrophosphate supplied through extruded rice kernels improves body iron stores in children: a double-blind, randomized, placebo-controlled midday meal feeding trial in Indian schoolchildren

Abstract: Regular intake of 19 mg Fe/d in MFPP supplied through extruded rice kernels improves iron stores and reduces iron deficiency among schoolchildren in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 25 publications
2
38
0
1
Order By: Relevance
“…Such efforts could also include novel methods to improve iron status as suggested by results from a recent study in Andhra Pradesh, India. That study showed significant improvements in body iron stores and reduction in iron deficiency in primary school-aged children when they were given micronized ferric pyrophosphate (fortified extruded rice kernels mixed with normal rice) through midday meal for 8 mo [46].…”
Section: Discussionmentioning
confidence: 94%
“…Such efforts could also include novel methods to improve iron status as suggested by results from a recent study in Andhra Pradesh, India. That study showed significant improvements in body iron stores and reduction in iron deficiency in primary school-aged children when they were given micronized ferric pyrophosphate (fortified extruded rice kernels mixed with normal rice) through midday meal for 8 mo [46].…”
Section: Discussionmentioning
confidence: 94%
“…In African settings, school feeding programs are shown to improve intake of energy [69] and micronutrients [5,22], such as calcium, vitamin C and vitamin A through the distribution of fruits or dairy products. Beneficial effects of fortified food distribution through school feeding programs on micronutrient status were reported [70,71]. Calcium supplementation showed positive effects on calcium bone acquisition of children accustomed to low-calcium diets [72,73] and on long-term bone mass growth [74].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reviews suggest that iron deficiencies in early life have persistent negative effects later in life [57,58]. The fortification of rice has proven to be effective in improving iron status for children (between 6 and 13 years old) in India when the fortified rice was provided, containing at least 17 mg to 19 mg iron through micronized ferrous pyrophosphate [29,59]. In Vietnam, where the diet provides approximately 4.8 mg of iron, if children age 6 to 59.9 months consumed fortified rice with micronized ferrous phosphate and sauces with NaFeEDTA, those products could provide, depending on the age groups, ranges of 2.7 mg to 7.4 mg, and 0.6 mg to 1.2 mg respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A market survey in Vietnam [21], commissioned in 2009 by the GAIN, showed potential for a multiple food fortification strategy due to highly concentrated industries for vegetable oil (8 producers with 95% of the market), fish sauces (13 producers with 60% of the market), flavoring powders (13 producers with 75% of the market), soy sauces (4 producers with 76% of the market) and wheat flour (8 producers with 84% of the market). In addition, rice fortification is currently getting more attention because fortification technology is now available [22,23,24,25], and new evidence is demonstrating the potential benefits of rice fortification to control micronutrient deficiencies [26,27,28,29]. …”
Section: Introductionmentioning
confidence: 99%